HIV elite control is associated with reduced TRAILshort expression. (1st September 2019) - Paim, Ana C.; Cummins, Nathan W.; Natesampillai, Sekar; Garcia-Rivera, Enrique; Kogan, Nicole; Neogi, Ujjwal; Sönnerborg, Anders; Sperk, Maike; Bren, Gary D.; Deeks, Steve; Polley, Eric; Badley, Andrew D.
Abstract : Objective: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) dependent apoptosis has been implicated in CD4 + T-cell death and immunologic control of HIV-1 infection. We have described a splice variant called TRAILshort, which is a dominant negative ligand that antagonizes TRAIL-induced cell death in the context of HIV-1 infection. HIV-1 elite controllers naturally control viral replication for largely unknown reasons. Since enhanced death of infected cells might be responsible, as might occur in situations of low (or inhibited) TRAILshort, we tested whether there was an association between elite controller status and reduced levels of TRAILshort expression. Design: Cohort study comparing TRAILshort and full length TRAIL expression between HIV-1 elite controllers and viremic progressors from two independent populations. Methods: TRAILshort and TRAIL gene expression in peripheral blood mononuclear cells (PBMCs) was determined by RNA-seq. TRAILshort and TRAIL protein expression in plasma was determined by antibody bead array and proximity extension assay respectively. Results: HIV-1 elite controllers expressed less TRAILshort transcripts in PBMCs ( P = 0.002) and less TRAILshort protein in plasma ( P < 0.001) than viremic progressors. Conclusion: Reduced TRAILshort expression in PBMCs and plasma is associated with HIV-1 elite controller status. Abstract : Supplemental Digital Content is available in the text